The Influence of Leadership Style, Supervision, and Work Motivation of the Madrasah Principals on Teacher Performance in Private Madrasah Aliyah in Wanasaba Subdistrict, East Lombok Regency - Imranfahrudi, Imranfahrudi; Al Idrus, S. Ali Jadid; Bahtiar, Bahtiar (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study aims to identify the influence of leadership style, supervision, and work motivation of the madrasah principals on teacher performance in Private Madrasah Aliyah (MA) in Wanasaba Subdistrict, East Lombok Regency. The research adopts a quantitative approach, with data collection conducted through questionnaires. Data analysis techniques include simple linear regression and multiple linear regression, calculated using SPSS 16.0. The results of the simple linear regression analysis are as follows: 1) There is a significant influence of the madrasah principal's leadership style on teacher performance, indicated by a sig. value of 0.000 < 0.05 and a t-value of 11.857 > 1.994 (t-value > t-table), with the influence of variable X1 on Y amounting to 65.8%. 2) There is a significant influence of the madrasah principal's supervision on teacher performance, indicated by a sig. value of 0.000 < 0.05 and a t-value of 13.285 > 1.994 (t-value > t-table), with the influence of variable X2 on Y amounting to 70.7%. 3) There is a significant influence of the madrasah principal's work motivation on teacher performance, indicated by a sig. value of 0.000 < 0.05 and a t-value of 11.097 > 1.994 (t-value > t-table), with the influence of variable X3 on Y amounting to 62.8%. 4) The results of the multiple linear regression analysis indicate that there is a significant combined influence of leadership style, supervision, and work motivation of the madrasah principals on teacher performance, with a sig. value of 0.000 < 0.05 and an F-value of 84.561 > 2.732 (F-value > F-table), and the combined influence of X1, X2, and X3 on Y amounting to 78.1%.